Discovery and Characterization of ACT‐451840: an Antimalarial Drug with a Novel Mechanism of Action. (29th July 2016) - Boss, Christoph; Aissaoui, Hamed; Amaral, Nathalie; Bauer, Aude; Bazire, Stephanie; Binkert, Christoph; Brun, Reto; Bürki, Cédric; Ciana, Claire‐Lise; Corminboeuf, Olivier; Delahaye, Stephane; Dollinger, Claire; et al.
Abstract: More than 40 % of the world's population is at risk of being infected with malaria. Most malaria cases occur in the countries of sub‐Saharan Africa, Central and South America, and Asia. Resistance to standard therapy, including artemisinin combinations, is increasing. There is an urgent need for novel antimalarials with new mechanisms of action. In a phenotypic screen, we identified a series of phenylalanine‐based compounds that exhibit antimalarial activity via a new and yet unknown mechanism of action. Our optimization efforts culminated in the selection of ACT‐451840 [( S, E )‐ N ‐(4‐(4‐acetylpiperazin‐1‐yl)benzyl)‐3‐(4‐( tert ‐butyl)phenyl)‐ N ‐(1‐(4‐(4‐cyanobenzyl)piperazin‐1‐yl)‐1‐oxo‐3‐phenylpropan‐2‐yl)acrylamide] for clinical development. Herein we describe our optimization efforts from the screening hit to the potential drug candidate with respect to antiparasitic activity, drug metabolism and pharmacokinetics (DMPK) properties, and in vivo pharmacological efficacy. Abstract : Do it the phenotypic way : After having failed by using a target‐based rational approach, we decided to go after malaria parasites by putting phenotypic assays at the center of our efforts. Herein you will learn the story behind the identification of ACT‐451840, which was selected for clinical development as an antimalarial drug candidate.